A Deep‐Blue‐Emitting Heteroatom‐Doped MR‐TADF Nonacene for High‐Performance Organic Light‐Emitting Diodes. (16th January 2023) - Madayanad Suresh, Subeesh; Zhang, Le; Hall, David; Si, Changfeng; Ricci, Gaetano; Matulaitis, Tomas; Slawin, Alexandra M. Z.; Warriner, Stuart; Olivier, Yoann; Samuel, Ifor D. W.; Zysman‐Colman, Eli
Abstract: We present a p‐ and n‐doped nonacene compound, NOBNacene, that represents a rare example of a linearly extended ladder‐type multiresonant thermally activated delayed fluorescence (MR‐TADF) emitter. This compound shows efficient narrow deep blue emission, with a λ PL of 410 nm, full width at half maximum, FWHM, of 38 nm, photoluminescence quantum yield, ΦPL of 71 %, and a delayed lifetime, τ d of 1.18 ms in 1.5 wt % TSPO1 thin film. The organic light‐emitting diode (OLED) using this compound as the emitter shows a comparable electroluminescence spectrum peaked at 409 nm (FWHM=37 nm) and a maximum external quantum efficiency (EQEmax ) of 8.5 % at Commission Internationale de l'Éclairage (CIE) coordinates of (0.173, 0.055). The EQEmax values were increased to 11.2 % at 3 wt % doping of the emitter within the emissive layer of the device. At this concentration, the electroluminescence spectrum broadened slightly, leading to CIE coordinates of (0.176, 0.068). Abstract : A deep blue boron‐, nitrogen‐ and oxygen‐doped nonacene emitter that shows multi‐resonant thermally activated delayed fluorescence (MR‐TADF) is described. The emitter shows bright, deep‐blue narrowband emission in an organic light emitting diode (OLED) device.